1988
DOI: 10.1161/01.atv.8.3.281
|View full text |Cite
|
Sign up to set email alerts
|

Antiatherogenic effect of olive and corn oils in cholesterol-fed rabbits with the same plasma cholesterol levels.

Abstract: Two groups of 18 rabbits were fed Isocalorlc, cholesterol-enriched diets for 8 weeks. The diet for one group was supplemented with 5% corn oil. The concentration of cholesterol in plasma was determined weekly and the amount of cholesterol In the diet was adjusted Individually so that each rabbit had a mean plasma cholesterol concentration of about 45 mM during the experimental period. The aortic cholesterol concentrations were 122 ± 29 and 193 ± 38 (mean ± SEM) /xmol/g protein for the cornoil group and the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…Similar to our study, others found that addition to the diet of cholesterol in an evaporable solvent without the use of additional fat resulted in a more atherogenic hypercholesterolemia than that produced when oils were used for the addition of cholesterol, although the plasma cholesterol level was higher in the group that received the additional fat. 53 Hypertriglyceridemia is accompanied by larger lipoprotein particles that reduce the influx of lipoprotein into the arterial wall, 54 and in study A of the present investigation, there was a more rapid rise in triacylglycerol concentration compared with that in study B (Table 1). We have previously suggested that this might explain why even small diet modifications influence the impairment of endothelial function in small arteries.…”
Section: Evidence For Diet-dependent Effect Of Endothelium-mediated Rmentioning
confidence: 43%
See 1 more Smart Citation
“…Similar to our study, others found that addition to the diet of cholesterol in an evaporable solvent without the use of additional fat resulted in a more atherogenic hypercholesterolemia than that produced when oils were used for the addition of cholesterol, although the plasma cholesterol level was higher in the group that received the additional fat. 53 Hypertriglyceridemia is accompanied by larger lipoprotein particles that reduce the influx of lipoprotein into the arterial wall, 54 and in study A of the present investigation, there was a more rapid rise in triacylglycerol concentration compared with that in study B (Table 1). We have previously suggested that this might explain why even small diet modifications influence the impairment of endothelial function in small arteries.…”
Section: Evidence For Diet-dependent Effect Of Endothelium-mediated Rmentioning
confidence: 43%
“…Furthermore, others found that the distribution of cholesterol between the plasma lipoproteins in the cholesterol-fed rabbits fed additional fat was similar to the rabbits fed a diet where cholesterol was added by use of ether. 53 Although speculative, the use of the vehicles in the present studies may have affected the levels of lipid peroxides present in the hypercholesterolemic rabbits, which have been reported to reduce PG and EDRF release in large arteries.…”
Section: Evidence For Diet-dependent Effect Of Endothelium-mediated Rmentioning
confidence: 85%
“…In contrast, a previous study suggests that the TPC concentration in rabbits fed polyunsaturated fat would be lower than those fed monounsaturated fat if similar cholesterol supplements were used (90). Two other studies have reported that the TPC concentration of monounsaturated fat-fed rabbits was intermediate between saturated fat-fed and polyunsaturated fat-fed rabbits (92,93).…”
Section: Discussionmentioning
confidence: 88%
“…Other studies of cholesterol-induced atherosclerosis in rabbits have reported a correlation between the accumulation of arterial cholesterol and the TPC concentration. However, polyunsaturated fat-fed animals had less atherosclerosis in one study, and monounsaturated fat-fed animals less in the other (90,92). The reason for these differences are not clear, but Kritchevsky has suggested that cholesterol-induced atherosclerosis in rabbits was sensitive to the ratio of dietary monounsaturated to saturated fats (29).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation